(untitled) (Global Journal of Science Frontier Research, 2016)
Life is but a continuous process of energy conversion, transformation and use. The quantity of energy, forms and the sources used for conversion from one form to other are closely linked with economy and quality of life. But the energy conversion, transformation and use always produce effects on the surrounding environment. Some of these effects are detrimental to human health and the environment. Environmental pollution, particularly global warming is the talk of the day. Burning of fossil fuels produce smokes (COx, NOx, SOx and undesirable particulates) or flue gas, ash and other wastes. The wastes, flue gas, particulates and radiation produced in the energy system, cause health hazards. The SOx and the NOx are responsible for acid rain.